The Penal Populism in The Changing Status of Papuan Criminal Armed Group (KKB Papua) into A Terrorist Organization - Leebarty Taskarina; Nuri Widiastuti Veronika (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2021)
The Indonesian government’s decision to change the status of Papuan Criminal Armed Group (KKB Papua) into a terrorist organization generated mixed responses. Over exposure on KKB Papua’s brutal acts by the media had showed a firm support for this decision and it had successfully influenced public opinion on justice and crime as well as contributed to deeper stigmatization towards the group. This status-changing decision signifies the penal populism policy, which was highly predisposed by political actors’ emotional state and ignored the legal mechanism to define a group as a terrorist organization (List of Suspected Terrorist and Terrorist Organizations). This paper analyzes government’s decision on KKB Papua’s status changing from penal populism point of view, where the construction of public’s punitive opinion had been highly dominated by the media. Employing a qualitative discourse analysis, this paper argues that the public anger, social discontent, and sentiments regarding a political event and the criminal justice system, had been justified as the “people’s will” which pushed government’s decision to determine KKB Papua as a terrorist organization. In turn, penal populism policy and media’s influence in presenting virtual reality to frame people's emotions had ultimately led to state hate crime against KKB Papua.